Victim Blaming terhadap Korban Kekerasan dalam Rumah Tangga; Tinjauan Hukum Positif dan Hukum Pidana Islam - Chairunnisa Nasution; Mar’ie Mahfudz Harahap (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2025)
This article aims to analyze and compare how Indonesian positive law and Islamic criminal law perceive and respond to the phenomenon of victim blaming against victims of domestic violence. The study adopts a qualitative method through a normative and comparative legal approach, based on statutory regulations, classical and contemporary Islamic jurisprudence literature, as well as academic journals published within the last ten years. The findings indicate that the practice of victim blaming not only exacerbates the psychological and social conditions of victims but also obstructs their access to justice. In the context of positive law, although Law Number Twenty-Three of the Year Two Thousand and Four provides a legal framework for the protection of domestic violence victims, its implementation still encounters challenges, including the persistence of patriarchal cultural norms, limited availability of legal assistance, and the lack of sensitivity among law enforcement personnel. On the other hand, Islamic criminal law upholds the principle of preserving the maqasid syariah, especially the protection of life and human dignity, and strictly prohibits domestic violence and the act of blaming victims, considering such behavior an act of injustice.